Epistemological contextualism - Blaauw, Martijn (Rodopi, 2005)
Contextualist theories of knowledge have received a lot of attention in the contemporary epistemological literature. The central idea of such theories is that contextual factors play an important role in determining whether a particular knowledge sentence is true or false. Thus, on contextualist theories of knowledge it might be the case that a particular subject knows a proposition in one context but fails to know that same proposition in another context-while the only thing that has changed is the context.Of the extant contextualist theories of knowledge, attributer contextualism (that is, t.
Keywords: Knowledge, Theory of.; Contextualism (Philosophy); Théorie de la connaissance.; Contextualisme (Philosophie); epistemology.; PHILOSOPHY -- Epistemology.; Knowledge, Theory of; Erkenntnistheorie; Erkenntnis; Kontextualismus